Tai Chi practice enables prefrontal cortex bilateral activation and gait performance prioritization during dual-task negotiating obstacle in older adults - Chen, Yan; Wan, Aiying; Mao, Min; Sun, Wei; Song, Qipeng; Mao, Dewei (Frontiers in Aging Neuroscience, 2022)
Background With aging, the cognitive function of the prefrontal cortex (PFC) declined, postural control weakened, and fall risk increased. As a mind–body exercise, regular Tai Chi practice could improve postural control and effectively prevent falls; however, underlying brain mechanisms remained unclear, which were shed light on by analyzing the effect of Tai Chi on the PFC in older adults by means of functional near-infrared spectroscopy (fNIRS). Methods 36 healthy older adults without Tai Chi experience were divided randomly into Tai Chi group and Control group. The experiment was conducted four times per week for 16 weeks; 27 participants remained and completed the experiment. Negotiating obstacle task (NOT) and negotiating obstacle with cognitive task (NOCT) were performed pre- and post-intervention, and Brodmann area 10 (BA10) was detected using fNIRS for hemodynamic response. A three-dimensional motion capture system measured walking speed. Results After intervention in the Tai Chi group under NOCT, the HbO2 concentration change value (ΔHbO2) in BA10 was significantly greater (right BA10: p = 0.002, left BA10: p = 0.001), walking speed was significantly faster (p = 0.040), and dual-task cost was significantly lower than pre-intervention (p = 0.047). ΔHbO2 in BA10 under NOCT was negatively correlated with dual-task cost (right BA10: r = −0.443, p = 0.021, left BA10: r = −0.448, p = 0.019). There were strong negative correlations between ΔHbO2 and ΔHbR under NOCT either pre-intervention (left PFC r = −0.841, p < 0.001; right PFC r = −0.795, p < 0.001) or post-intervention (left PFC r = −0.842, p < 0.001; right PFC r = −0.744, p < 0.001). Conclusion Tai Chi practice might increase the cognitive resources in older adults through the PFC bilateral activation to prioritize gait performance during negotiating obstacles under a dual-task condition.